2009
DOI: 10.1007/s10792-009-9327-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estrogen replacement therapy on lens epithelial cell apoptosis in an experimental rat model

Abstract: Epidemiologic studies have revealed a higher incidence of cataracts in estrogen-deprived postmenopausal women, although the pathogenic mechanism has not yet been elucidated. Apoptosis of lens epithelial cells has been associated with cataractogenesis. The aim of the study reported here was to investigate the effect of estrogen replacement therapy (ERT) on lens epithelial cell apoptosis in an experimental rat model. Forty female Wistar rats were randomized into four groups: ERT (17beta-estradiol, 10 microg/kg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…In the presented study it was noted that oral administration of estradiol did not affect oxidative stress-related parameters in the lenses of ovariectomized rats, including the GSH content. Similar findings were made in another study, in which estradiol administered to estrogen-deficient rats revealed no effect on apoptosis rate in the lens epithelial cells, which was increased in the ovariectomized control rats [67]. Unlike the treatment with estradiol, administration of sinapic acid at both doses caused a significant increase in the estradiol concentration in the serum of the ovariectomized rats [21].…”
Section: Discussionsupporting
confidence: 80%
“…In the presented study it was noted that oral administration of estradiol did not affect oxidative stress-related parameters in the lenses of ovariectomized rats, including the GSH content. Similar findings were made in another study, in which estradiol administered to estrogen-deficient rats revealed no effect on apoptosis rate in the lens epithelial cells, which was increased in the ovariectomized control rats [67]. Unlike the treatment with estradiol, administration of sinapic acid at both doses caused a significant increase in the estradiol concentration in the serum of the ovariectomized rats [21].…”
Section: Discussionsupporting
confidence: 80%
“…Oestrogen and progesterone receptor mRNAs are present in retinal, ciliary body, iris and lens epithelial cells 10 . In an experimental rat model, oestrogen had a protective effect against the apoptosis of lens epithelial cells 11 . Moreover, some laboratory studies have suggested that oestrogen may provent cataract formation 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…In an experimental rat model, estrogen exerted a protective effect against the apoptosis of lens epithelial cells [ 8 ]. Estrogen modulates the immune response by regulating the expression and secretion of inflammatory cytokines [ 9 ].…”
Section: Introductionmentioning
confidence: 99%